2*sqrt(27) - sqrt(3) = 2*sqrt(9*3) - sqrt(3) = 2*sqrt(9)*sqrt(3) - sqrt(3)
= 2*3*sqrt(3) - sqrt(3) - 6*sqrt(3) - srt(3) = 5*sqrt(3)
Chat with our AI personalities
Yes. A simple example: sqrt(2)*sqrt(2) = 2 This property is used to "simplify" (rationalise the denominator of) surds.
13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer
27 over 54 simplifies to 1 over 2. 27/54 = 27/(2 x 27) simplify up and down 27, you will get 1/2 27/54 = 1/2
Surds are normally irrational numbers but they can be simplified for instance the square root of 12 can be expressed as 2 times the square root of 3
The numbers are: -2 +2*sq rt 19 and -2 -2*sq rt 19 Check: (-2 +2*sq rt 19)*(-2 -2*sq rt 19) = -72 and (-2 +2*sq rt 19)+(-2 -2*sq rt 19) = -4